Galáxias Neobarrocas: poesia e visualidade em Haroldo de Campos - Andrade Júnior, Antonio Francisco de (2006)
The present work aims at making a critical-interpretative analysis of a certain part of Haroldo de Campos poetic production especially the book Crisantempo that represents the overlapping between the concrete formal racionalism and the convulsive look which is characteristic of the visual neobaroque experience, evidencing thus the tensions between invention and techinique, chaos and order, concentration and excess, form and inform. Articulating, therefore, the theoretical discussion around the relations between poetry and image to issues raised by the haroldian critique, the intended goal is to show the importance of these tensions for the reading of poems that are related to the visual issue, especially those which promote the dialogue between poetic and pictorial language.